KAJIAN SINKRONISASI ANTARA PERENCANAAN DAN KEBUTUHAN ALAT KESEHATAN DI RUMAH SAKIT TINGKAT III TNI AL DI ERA JKN PERIODE 2020 - Ningsih, Ita Trismiati; Delina Hasan; Prih Sarnianto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Health equipment will be effective if it is adjusted to the needs of each hospital, with increasing servicedemands, incomplete medical devices can cause problems in service, and become complaints of patientswho come for treatment at the hospital, including JKN patients. within the Indonesian Navy. This studyaims to determine the synchronization between planning and the need for medical devices at the TNI ALLevel III Hospital in 2020. This study used a quantitative descriptive method with retrospective datacollection on medical devices at five Level III TNI AL Hospitals, namely the TNI AL Hospital Dr. .Komang Makes (Belawan, North Sumatra), Dr. Oepomo (Surabaya, East Java), Samuel J. Moeda(Kupang, East Nusa Tenggara), Marine Ewa Pangalila (Surabaya, East Java), Merauke (Merauke). Theanalysis shows that planning guidelines, sources of funds, coordination, planning preparation, planningmethods, planning documents, distribution are in accordance with Minister of Defense Regulation No. 11of 2014. Thus, it can be concluded that the condition of medical devices in five level III hospitals of theIndonesian Navy in 2020 is appropriate in terms of the Minister of Defense Regulation No. 11 of 2014,there is a synchronization between planning and the need for medical equipment in the JKN era, and theTNI AL Level III Hospital is ready to cooperate with BPJS Health.